Pemodelan Tarikan Perjalanan Mahasiswa Dan Karyawan Program Studi Teknik Sipil - Ikhwanuddin Ikhwanuddin (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
This study aims to develop a trip attraction model for students and employees traveling to the Civil Engineering Study Program, Faculty of Engineering, Universitas Brawijaya; identify transportation mode choice characteristics; and analyze the distribution of users’ residential distances from the campus. The study was conducted through a questionnaire survey involving 30 respondents, consisting of 28 students and 2 employees. The data used in this study comprised primary data on travel characteristics and transportation modes, as well as secondary data on the number of students and employees, number of classes, building floor area, and parking area. The trip attraction model was developed using linear regression analysis with the assistance of IBM SPSS Statistics 26, while the travel distribution pattern was analyzed based on the respondents’ residential distances from the campus. The results indicate that motorcycles were the most dominant mode of transportation, accounting for approximately 67% of total trips, while walking, cars, and public transportation accounted for smaller proportions. None of the respondents used bicycles; therefore, a trip attraction model for bicycle travel could not be developed. The variables used in the modeling included the number of students and employees, number of classes, building floor area, and vehicle parking area. Based on the distribution of respondents’ residences, 16 respondents lived less than 3 km from the campus, 14 respondents lived 3.1–7 km away, while 1 respondent lived 7.1–10 km away and another lived more than 10 km away. These findings indicate that most trips to the campus originate from relatively nearby areas and may potentially contribute to traffic congestion during peak hours. The results of this study can serve as a consideration for transportation management and the planning of mobility-supporting facilities in the vicinity of the Civil Engineering Study Program at Universitas Brawijaya.